Pengaruh Senam Nifas Kombinasi Rendam Kaki terhadap Peningkatan Kualitas Tidur Ibu Postpartum - Putri, Vina Della Septiana Agustini; Keswara, Nila Widya; Prisusanti, Retno Dewi (Fakultas Ilmu Keperawatan Universitas Klabat, 2026)
The postpartum period is a time of physiological and psychological adjustment that affects a mother’s sleep quality. Sleep disturbances often occur due to hormonal changes, fatigue, and nighttime breastfeeding. This study aimed to determine the effect of a combination of postpartum exercises and warm foot soaks on the sleep quality of postpartum mothers at the Sri Wahyuni Kalipare Maternity and Child Health Clinic in Malang Regency. A quantitative method with a pre-experimental one-group pretest–posttest design was used. The sample consisted of 24 postpartum mothers selected using consecutive sampling. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention. The intervention consisted of 15–20 minutes of postpartum exercise and 10–20 minutes of foot soaking for 7 days. Analysis was performed using the Wilcoxon signed-rank test. The results showed that before the intervention, all respondents had poor sleep quality. After the intervention, 70% experienced an improvement to good sleep quality. Statistical analysis revealed a p-value of 0.000 (p < 0.05). It was concluded that the combination of interventions can improve sleep quality in postpartum mothers. Masa nifas merupakan periode adaptasi fisiologis dan psikologis yang mempengaruhi kualitas tidur ibu. Gangguan tidur sering terjadi akibat perubahan hormonal, kelelahan, dan aktivitas menyusui malam hari. Penelitian ini bertujuan mengetahui pengaruh senam nifas kombinasi rendam kaki air hangat terhadap kualitas tidur ibu postpartum di TPMB Sri Wahyuni Kalipare Kabupaten Malang. Metode yang digunakan adalah kuantitatif dengan desain pre-experimental one group pretest–posttest. Sampel sebanyak 24 ibu postpartum dengan teknik consecutive sampling. Kualitas tidur diukur menggunakan Pittsburgh Sleep Quality Index (PSQI) sebelum dan sesudah intervensi. Intervensi berupa senam nifas 15–20 menit dan rendam kaki 10–20 menit selama 7 hari. Analisis menggunakan uji wicolxon ranged-sign test. Hasil menunjukkan sebelum intervensi seluruh responden memiliki kualitas tidur buruk. Setelah intervensi, 70% mengalami peningkatan menjadi baik. Uji statistik menunjukkan p-value 0,000 (p<0,05). Disimpulkan bahwa kombinasi intervensi dapat meningkatkan kualitas tidur ibu postpartum.